Biomechanical analysis of weighted-ball exercises for baseball pitchers - Fleisig, G. S.; Diffendaffer, A. Z.; Aune, K. T.; Ivey, B.; Laughlin, W. A. (Sports Health: A Multidisciplinary Approach, 2017)
Background: Weighted-ball throwing programs are commonly used in training baseball pitchers to increase ball velocity. The purpose of this study was to compare kinematics and kinetics among weighted-ball exercises with values from standard pitching (ie, pitching standard 5-oz baseballs from a mound). Hypothesis: Ball and arm velocities would be greater with lighter balls and joint kinetics would be greater with heavier balls. Study Design: Controlled laboratory study. Methods: Twenty-five high school and collegiate baseball pitchers experienced with weighted-ball throwing were tested with an automated motion capture system. Each participant performed 3 trials of 10 different exercises: pitching 4-, 5-, 6-, and 7-oz baseballs from a mound; flat-ground crow hop throws with 4-, 5-, 6-, and 7-oz baseballs; and flat-ground hold exercises with 14- and 32-oz balls. Twenty-six biomechanical parameters were computed for each trial. Data among the 10 exercises were compared with repeated measures analysis of variance and post hoc paired t tests against the standard pitching data. Results: Ball velocity increased as ball mass decreased. There were no differences in arm and trunk velocities between throwing a standard baseball and an underweight baseball (4 oz), while arm and trunk velocities steadily decreased as ball weight increased from 5 to 32 oz. Compared with values pitching from a mound, velocities of the pelvis, shoulder, and ball were increased for flat-ground throws. In general, as ball mass increased arm torques and forces decreased; the exception was elbow flexion torque, which was significantly greater for the flat-ground holds. There were significant differences in body positions when pitching on the mound, flat-ground throws, and holds. Conclusions: While ball velocity was greatest throwing underweight baseballs, results from the study did not support the rest of the hypothesis. Kinematics and kinetics were similar between underweight and standard baseballs, while overweight balls correlated with decreased arm forces, torques, and velocities. Increased ball velocity and joint velocities were produced with crow hop throws, likely because of running forward while throwing. Clinical Relevance: As pitching slightly underweight and overweight baseballs produces variations in kinematics without increased arm kinetics, these exercises seem reasonable for training pitchers. As flat-ground throwing produces increased shoulder internal rotation velocity and elbow varus torque, these exercises may be beneficial but may also be stressful and risky. Flat-ground holds with heavy balls should not be viewed as enhancing pitching biomechanics, but rather as hybrid exercises between throwing and resistance training.